Haloacetic acids in drinking water and risk for stillbirth - King, W (BMJ Group, 2005)
Aims: To investigate the effects of haloacetic acid (HAA) compounds in drinking water on stillbirth risk. Methods: A population based case-control study was conducted in Nova Scotia and Eastern Ontario, Canada. Estimates of daily exposure to total and specific HAAs were based on household water samples and questionnaire information on water consumption at home and work. Results: The analysis included 112 stillbirth cases and 398 live birth controls. In analysis without adjustment for total THM exposure, a relative risk greater than 2 was observed for an intermediate exposure category for total HAA and dichloroacetic acid measures. After adjustment for total THM exposure, the risk estimates for intermediate exposure categories were diminished, the relative risk associated with the highest category was in the direction of a protective effect, and all confidence intervals included the null value. Conclusions: No association was observed between HAA exposures and stillbirth risk after controlling for THM exposures.